Effect of Replacement of Maize with Soybean Hulls in the Concentrate Mixture of Buffalo Calves - Jadhav, S.K.; Dhok, A.P.; Deshmukh, A.D.; Lende, S.R.; Taksande, P.E. (Indian Journal of Animal Nutrition, 2018)
The study was conducted on twelve growing buffalo calves, aged around one year with 127.17 kg body weight to evaluate the effect of replacement of maize with soybean hulls in the concentrate mixture. The calves were randomly distributed in two groups and fed for 90 days to meet the requirements. The animals in control group (T1) were given concentrate mixture containing 40% maize and in group T2 corn was replaced by soybean hulls at 75% level (Table 1). The calves in both the groups were offered gram straw and para grass. The DM intake, average daily gain and feed conversion ratio were similar in both the groups. The rumen fermentation parameters viz., pH, NH3-N and TVFA concentration were alike. There were no significant differences with regards to serum calcium, phosphorus, total protein and albumin: globulin ratio. The cost of production per kg gain was lower (P<0.05) in group fed soybean hulls than that of control. It was concluded that the soybean hulls can replace corn upto 75% as an energy source in the concentrate mixture for economical raising of growing buffalo calves.